2011
DOI: 10.1186/1471-2148-11-127
|View full text |Cite
|
Sign up to set email alerts
|

On the genome constitution and evolution of intermediate wheatgrass (Thinopyrum intermedium: Poaceae, Triticeae)

Abstract: BackgroundThe wheat tribe Triticeae (Poaceae) is a diverse group of grasses representing a textbook example of reticulate evolution. Apart from globally important grain crops, there are also wild grasses which are of great practical value. Allohexaploid intermediate wheatgrass, Thinopyrum intermedium (2n = 6x = 42), possesses many desirable agronomic traits that make it an invaluable source of genetic material useful in wheat improvement. Although the identification of its genomic components has been the objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 77 publications
6
74
1
2
Order By: Relevance
“…The previous cpDNA studies on the Triticeae (e.g. Adderley and Sun 2014;Mahelka et al 2011;Mason-Gamer 2013;Redinbaugh et al 2000;Yan and Sun 2012) have shown that during the allopolyploid formation the chloroplast genomes were inherited from the parent carrying the St (nuclear) genome. Hence, the allopolyploid St-containing genera, delimited on the basis of genomic composition, probably share the same (or very closely related) chloroplast genomes that originate from Pseudoroegneria.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous cpDNA studies on the Triticeae (e.g. Adderley and Sun 2014;Mahelka et al 2011;Mason-Gamer 2013;Redinbaugh et al 2000;Yan and Sun 2012) have shown that during the allopolyploid formation the chloroplast genomes were inherited from the parent carrying the St (nuclear) genome. Hence, the allopolyploid St-containing genera, delimited on the basis of genomic composition, probably share the same (or very closely related) chloroplast genomes that originate from Pseudoroegneria.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
“…Such species-specific mutations were already reported for the chloroplast genome. Mahelka et al (2011) separated L. elongatum and T. bessarabicum from P. strigosa on the basis of the trnL-trnF sequences. MasonGamer (2013) found chloroplast mutations that separated E. caninus and E. repens from L. elongatum, T. bessarabicum and P. strigosa.…”
Section: Dna Barcodingmentioning
confidence: 99%
“…Reticulate evolution or hybrid speciation was postulated to have occurred frequently during plant evolution (Kellogg and Bennetzen, 2004;Linder and Rieseberg, 2004;Mallet, 2005). In the Triticeae, it may have occurred in diploid species (Kellogg et al, 1996;Escobar et al, 2011), but it has been most frequently postulated for allopolyploid Triticeae genera (Kellogg et al, 1996;Mason-Gamer, 2004;Mason-Gamer et al, 2010;Mahelka et al, 2011). Reticulate or hybrid speciation can occur (reviewed in Linder and Rieseberg, 2004) as a consequence of allopolyploidization, which involves fusion of unreduced gametes, or instant genome duplication after fusion of haploid gametes, giving rise to a fertile hybrid species in which diploid parental genomes are maintained.…”
Section: What Mechanisms Have Shaped the Modern Rye Genome?mentioning
confidence: 99%
“…It is clearly one progenitor of most of the polyploids in Elymus s.l. , 2010a, 2010b and Thinopyrum (Liu and Wang 1993;Mahelka et al 2011). Not surprisingly, because it has so many polyploid derivatives, the exact delimitation of Pseudoroegneria and its descendants has been controversial, with some species placed in Elytrigia and others in Elymus.…”
Section: Psathyrostachys Nevskimentioning
confidence: 97%